Acute Encephalopathy With Biphasic Seizures and Late Reduced Diffusion Associated With Adenoviral Pneumonia. (5th February 2019) - Lee, Keun Soo; Lee, Bo Lyun; Heo, Young Jin
Acute encephalopathy with biphasic seizures and late reduced diffusion is a subtype of acute encephalopathy described in a cohort of Japanese children. Few cases have been reported in countries other than Japan. It is characterized clinically by biphasic seizures and late reduced subcortical diffusion on magnetic resonance imaging (MRI). We report the case of a 3-year-old Korean girl with acute encephalopathy with biphasic seizures and late reduced diffusion who presented with status epilepticus associated with fever and pneumonia. Human adenovirus was detected from a respiratory specimen using multiplex real-time reverse transcriptase polymerase chain reaction. After 5 days, she developed a second cluster of seizures followed by altered consciousness, aphasia, stereotypic movement, and developmental regression. Her brain MRI showed symmetrical and extensive restricted diffusion in the subcortical white matter, which finally resulted in global brain atrophy, consistent with acute encephalopathy with biphasic seizures and late reduced diffusion. Here, we report a case of acute encephalopathy with biphasic seizures and late reduced diffusion associated with preceding adenoviral pneumonia.